PROBLEMS OF CONSTITUTIONALISM IN THE REPUBLIC OF KYRGYZSTAN - SHUKURALIEVA, Nartsiss (CENTRAL ASIA AND THE CAUCASUS, 2007)
The transformation and democratization processes have given rise to several regimes that are difficult to define and cannot be classified in the traditional categories of totalitarianism, authoritarianism, and democracy. Contradictory types of democratic and nondemocratic regimes are creating unusual political systems that can be defined as “hybrid regimes,” “imitative democracies,” or “delegative democracies.” The ambiguity of these regimes is making it difficult to classify them according to the well-known categories. On the one hand, they contain many elements characteristic of an authoritarian regime, while on the other, they appear to be close to democracy. As J. Linz showed,1 the authoritarian elements are related to the instability of the political system, the continuous constitutionalizing of which has introduced ambiguity into the rules of the game. The democratic elements, in turn, are related to the declared adherence to the democratic idea expressed in constant political revision of the constitutional norms. This situation, which is typical of many states (not only of hybrid, but also of democratic regimes), is manifested very clearly in Kyrgyzstan. The political system that has been forming in Kyrgyzstan for 16 years is akin to a “mobile, chaotic” regime. Amendments and addenda were made to the Constitution almost every two years (1994, 1996, 1998, 2001, 2003, 2006, 2007) and almost every time the interrelations among the branches of government and their powers underwent dramatic changes. All the novelizations,2 however, were introduced in their own “particular” way—with violation of the constitutional procedures for making amendments and addenda. Moreover, the political system was essentially not regulated by the Constitution, but by the law for putting the Constitution into effect. This law, in turn, established entirely different, and at times contradictory, adaptive-temporary provisions. This was compounded by the differences in the Constitution texts in the Kyrgyz (state) and the Russian (official) language. Theoretically, the Constitution in the Kyrgyz language dominated and was considered the main document. In practice, however, despite the principal contradictions in content, both versions were in effect at the same level.3 A situation developed in which the formal-legal side of political life consisted of several layers (or elements): constitutional, legislative, presidential decrees with statutory force,4 and by-laws. Each layer was horizontally and vertically unstable and mobile, frequently contradicting the others, and seemed to live a life of its own.